Effects of Gradient Coil Noise and Gradient Coil Replacement on the Reproducibility of Resting State Networks - Bagarinao, Epifanio; Tsuzuki, Erina; Yoshida, Yukina; Ozawa, Yohei; Kuzuya, Maki; Otani, Takashi; Koyama, Shuji; Isoda, Haruo; Watanabe, Hirohisa; Maesawa, Satoshi; Naganawa, Shinji; Sobue, Gen (Frontiers in Human Neuroscience, 2018)
The stability of the MRI scanner throughout a given study is critical in minimizing hardware-induced variability in the acquired imaging data set. However, MRI scanners do malfunction at times, which could generate image artifacts and would require the replacement of a major component such as its gradient coil. In this paper, we examined the effect of low intensity, randomly occurring hardware-related noise due to a faulty gradient coil on brain morphometric measures derived from T1-weighted images and resting state networks (RSN) constructed from resting state functional MRI. We also introduced a method to detect and minimize the effect of the noise associated with a faulty gradient coil. Finally, we assessed the reproducibility of these morphometric measures and RSNs before and after gradient coil replacement. Our results showed that gradient coil noise, even at relatively low intensities, could introduce a large number of voxels exhibiting spurious significant connectivity changes in several RSNs. However, censoring the affected volumes during the analysis could minimize, if not completely eliminate, these spurious connectivity changes and could lead to reproducible RSNs even after gradient coil replacement.